Clinical Assessment of Scapula and Hip Joint Function in Preadolescent and Adolescent Baseball Players. (October 2014) - Beckett, Michael; Hannon, Michael; Ropiak, Christopher; Gerona, Christopher; Mohr, Karen; Limpisvasti, Orr
Background: Proper scapulothoracic and hip mechanics are essential aspects of the throwing kinetic chain. Little is known regarding these entities in preadolescent and adolescent baseball players. Hypothesis: Scapular malposition and dyskinesis as well as hip dysfunction are highly prevalent in preadolescent and adolescent baseball players and may be identified by simple clinical testing. Study Design: Descriptive laboratory study. Methods: A total of 112 baseball players aged 7 to 18 years were recruited from local Little Leagues, traveling teams, and high schools. Participants were divided into 2 groups: preadolescents (players aged 7-12 years) and adolescents (players aged 13-18 years). Scapular symmetry was tested with the yes/no method of Kibler and by measuring forward shoulder posture via the "coracoid distance." Hip abductor strength was measured by use of a handheld digital dynamometer. Functional gluteal and core strength was assessed by video analysis of the subjects performing the single-legged squat test. Hip range of motion was measured in the prone position by use of a handheld goniometer. Results: Compared with the preadolescent group, the adolescent group had a significantly higher prevalence of scapular dyskinesis in the throwing shoulder (50% vs 25.9%, P = .011). The adolescents had significantly higher normalized hip abduction strength in both the stride (17.41 vs 12.62 N/kg, P < .001) and stance (17.82 vs 12.61 N/kg, P < .001) legs. The preadolescent group was unable to perform the single-legged squat test correctly in either the stance (0% preadolescent vs 13% adolescent, P = .0127) or stride (0% preadolescent vs 9.3% adolescent, P = .0567) leg. The mean coracoid distance was elevated in the dominant (throwing) shoulder after controlling for scapular dyskinesis ( P < .0001). Presence of scapular dyskinesis was associated with a higher mean coracoid distance ( P = .0067). Conclusion: There was a high prevalence of dominant shoulder scapular dyskinesis in the adolescent compared with the preadolescent group, as well as universally poor single-legged squat test performance. The mean coracoid distance was higher in the dominant or throwing side compared with the nondominant side independent of scapular dyskinesis. Presence of scapular dyskinesis was associated with higher mean coracoid distance. Clinical Relevance: Identification of players thought to be at increased risk for throwing injuries and initiation of targeted rehabilitation programs may decrease injury rates in preadolescent and adolescent baseball players.